P596 Ustekinumab and anti-TNF agents are equally safe and effective in elderly Crohn's disease patients: A propensity adjusted multi-centre cohort study. (30th January 2023) - Gebeyehu, G G; Broglio, G; Liu, E; Limdi, J K; Selinger, C; Fiske, J; Razsanskaite, V; Smith, P J; Flanagan, P K; Subramanian, S
Abstract: Background: Anti-tumour necrosis factor (anti-TNF) agents are associated with increased infection risk among elderly inflammatory bowel disease (IBD) patients and thus alternative biologics may be preferable. Previous cohort studies have demonstrated a superior safety profile for vedolizumab compared to anti-TNF agents in the elderly. However, there is limited comparative data on the safety and effectiveness of ustekinumab in elderly IBD patients. We aimed to compare the safety and effectiveness of ustekinumab and anti-TNF agents in elderly Crohn's disease (CD) patients. Methods: Patients ≥60 years old who commenced ustekinumab or an anti-TNF agent for CD were included in this multi-centre retrospective cohort study. The primary outcome was time to development of any infection. Secondary outcomes included incidence of serious infections, defined as requiring hospitalisation and effectiveness assessed by treatment persistence and clinical response rates. We appropriately adjusted for confounders using propensity score matched analysis weighted by the inverse predicted probability of treatment weighting and performed a logistic regression analysis to assess factors associated with infections and treatment persistence. Results: 83 patients treated with ustekinumab and 124 patients (30 infliximab and 94 adalimumab) treated with anti-TNF therapy were included. A greater proportion of patients treated with ustekinumab were on concomitant steroids at baseline (37% vs 7.3%, p<0.001). After propensity adjustment, the infection free survival at 12 months was comparable between ustekinumab and anti-TNF agents (HR 0.79, 95% CI 0.58-1.07, p=0.128). Serious infection rate for ustekinumab was 7.55/100 patient years and 5.30/100 for anti-TNFs (p=0.3). None of the variables including Charlson co-morbidity index were associated with infection risk in a multi-variable model. Unadjusted treatment persistence rates at 12 months were lower for ustekinumab compared to anti-TNF agents (68.1% vs 82.8% respectively, p=0.020). After propensity adjustment, there was no difference in treatment persistence at 6 months (OR 1.23, 95% CI 0.37-4.10, p=0.741) and 12 months (OR 1.07, 95% CI 0.45-2.55, p=0.9). There was a significant reduction in HBI at 6 and 12 months compared to baseline in both groups (p<0.001). In a multivariable model, only concomitant thiopurine use was associated with treatment persistence at 12 months (OR 4.6, 95% CI 1.2-30.3, p=0.049). Conclusion: We observed comparable safety and effectiveness in a propensity score adjusted comparison of ustekinumab and anti-TNF treated elderly CD patients. The rates of serious infections were comparable between the two groups.